TRANSLATION PROBLEMS AND SOLUTIONS - Rustamova, Shahnoza; Turg`unova Fazilat Rustam qizi (Журнал иностранных языков и лингвистики, 2023)
Unfortunately, due to the cultural, linguistic, and stylistic distance between these two languages, translations between Uzbek and English are problematic. Both Uzbek and English belong to different language families; Therefore, translators can choose Uzbek when English expressions are not similar to each other, or vice versa. Translation problems are often exacerbated when translators are confronted with cultural words that contain hidden meanings. These problems can be partly due to the translator not having enough information about the source culture or being absent altogether. The more the translator is aware of the cultural differences between different languages, the better they produce translations.,